Racial Differences in Public Support for Federal Law Enforcement Finding and Prosecuting the January 6th Insurrectionists Who Broke Into the U.S. Capitol - Updegrove, Alexander H. (Crime & delinquency, 2025)
Black people may view the January 6th, 2021, attack on the U.S. Capitol as the latest development in a long series of threats that white supremacy poses to their status in the U.S., whereas white people may apply a colorblind perspective. Thus, Black people were hypothesized to support prosecuting insurrectionists at higher rates than white people because they want the federal government to protect Black people’s status. Results from a nationally representative dataset revealed that while a majority of both Black and white participants considered it very important for federal law enforcement agencies to find and prosecute those who broke into the Capitol, the odds of Black participants endorsing this view were 72% greater than the odds for white people.